Depletion of T cells via Inducible Caspase 9 Increases Safety of Adoptive T-Cell Therapy Against Chronic Hepatitis B - Klopp, Alexandre; Schreiber, Sophia; Kosinska, Anna D.; Pulé, Martin; Protzer, Ulrike; Wisskirchen, Karin (Frontiers in Immunology, 2021)
T-cell therapy with T cells that are re-directed to hepatitis B virus (HBV)-infected cells by virus-specific receptors is a promising therapeutic approach for treatment of chronic hepatitis B and HBV-associated cancer. Due to the high number of target cells, however, side effects such as cytokine release syndrome or hepatotoxicity may limit safety. A safeguard mechanism, which allows depletion of transferred T cells on demand, would thus be an interesting means to increase confidence in this approach. In this study, T cells were generated by retroviral transduction to express either an HBV-specific chimeric antigen receptor (S-CAR) or T-cell receptor (TCR) and in addition either inducible caspase 9 (iC9) or herpes simplex virus thymidine kinase (HSV-TK) as a safety switch. Real-time cytotoxicity assays using HBV-replicating hepatoma cells as targets revealed that activation of both safety switches stopped cytotoxicity of S-CAR- or TCR-transduced T cells within less than one hour. In vivo, induction of iC9 led to a strong and rapid reduction of transferred S-CAR T cells adoptively transferred into AAV-HBV-infected immune incompetent mice. One to six hours after injection of the iC9 dimerizer, over 90 % reduction of S-CAR T cells in the blood and the spleen and of over 99 % in the liver was observed limiting hepatotoxicity and stopping cytokine secretion. Simultaneously, however, the antiviral effect of S-CAR T cells was diminished because remaining S-CAR T cells were mostly non-functional and could not be restimulated with HBsAg. A second induction of iC9 was only able to deplete T cells in the liver. In conclusion, T cells co-expressing iC9 and HBV-specific receptors efficiently recognize and kill HBV-replicating cells. Induction of T-cell death via iC9 proved to be an efficient means to deplete transferred T cells in vitro and in vivo containing unwanted hepatotoxicity.